An investigation into the influence of particle properties and operating conditions on gas-solid flow phenomena - Anantharaman, Aditya (2017)
Horizontal pneumatic conveying and fluidization are two important gas-solid flow operations employed in wide-ranging industries from agro-processing to pharmaceutical and oil and gas. Despite being employed in industry for decades, they are still largely run on rules-of-thumb and experience rather than scientific principles. This research effort endeavors to contribute to their physical understanding by analyzing the effects of particle properties and varying operating conditions on these phenomena. This thesis is divided into three parts focusing on horizontal pneumatic conveying, fluidization and reactor modeling respectively. Part I deals with the minimum pickup velocity (Upu), defined as the minimum gas velocity required to initiate motion of a particle initially at rest, a very important parameter in horizontal pneumatic conveying. In this section, firstly, the effect of continuous particle size distribution (PSD) and particle shape on Upu is studied, where the involvement of inter-particle momentum transfer and particle rotation and lift is revealed. Secondly, the effect of particle diameter, density and shape on Upu is studied by investigating binary mixtures. Thirdly, the Upu of nanoparticles is reported for the first time and behavioral differences between polar and apolar nanoparticles are noted. Finally, the knowledge gap in Upu at the nano- and micro- scales is bridged by investigating particles from diameters 5 nm to 110,000 nm and the Three-zone Model developed for the micro-scale is modified to incorporate nanoparticles. Part II discusses the minimum fluidization velocity (Umf), and differential pressure signals and radial mass flux distribution in circulating fluidized beds (CFBs). Specific studies include the following: (i) a comparative analysis of the predictions of over a hundred empirical correlations to determine Umf with respect to Geldart Groups A, B and D, and bed voidage and particle sphericity; and (ii) investigating the effects of particle properties, namely, particle diameter and density, and varying operating conditions, namely, superficial gas velocity and overall mass flux on differential pressure signals (via Discrete Fourier Transform and Wavelet Decomposition) and the radial mass flux behavior of particles in a pilot-scale CFB riser. Part III attempts numerical modeling of a carbon-dioxide (CO2) methanation bubbling fluidized bed reactor. The effects of operating conditions like the temperature, pressure, and inlet feed ratio, and hydrodynamic parameters like the inlet feed rate, superficial gas velocity, particle diameter, particle density, particle sphericity and the bed voidage at minimum fluidization on methane production by the Sabatier reaction are studied through a heterogeneous bubbling fluidized bed reactor model. The physical understanding on horizontal pneumatic conveying and fluidization presented in this thesis is expected to contribute to the database and aid future researchers as well as designers of systems employing these operations.